Recent advances in palladium-catalysed asymmetric 1,4–additions of arylboronic acids to conjugated enones and chromones - Bartáček, Jan; Svoboda, Jan; Kocúrik, Martin; Pochobradský, Jaroslav; Čegan, Alexander; Sedlák, Miloš; Váňa, Jiří (Beilstein Journal of Organic Chemistry, 2021)
The transition metal (palladium)-catalysed asymmetric 1,4-addition of arylboronic acids to conjugated enones belong to the most important and emerging strategies for the construction of C–C bonds in an asymmetric fashion. This review covers known catalytic systems used for this transformation. For clarity, we are using the type of ligand as a sorting criterion. Finally, we attempted to create a flowchart facilitating the selection of a suitable ligand for a given combination of enone and arylboronic acid.
Keywords: asymmetric reaction; boronic acid; conjugated enones; chromones; enantioselective catalysis; Michael addition; Pd complexes